2021
DOI: 10.3390/ijerph182111100
|View full text |Cite
|
Sign up to set email alerts
|

Evidence Map and Systematic Review of Disinfection Efficacy on Environmental Surfaces in Healthcare Facilities

Abstract: Healthcare-associated infections (HAIs) contribute to patient morbidity and mortality with an estimated 1.7 million infections and 99,000 deaths costing USD $28–34 billion annually in the United States alone. There is little understanding as to if current environmental surface disinfection practices reduce pathogen load, and subsequently HAIs, in critical care settings. This evidence map includes a systematic review on the efficacy of disinfecting environmental surfaces in healthcare facilities. We screened 17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 211 publications
(370 reference statements)
0
5
0
1
Order By: Relevance
“…Recently an exhaustive review of studies on anti-infection procedures revealed they were based more on laboratory data rather than in situ efficacy ( 14 ). The authors advised practitioners and researchers to consider system-level efficacy and not just the efficacy of a focal setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently an exhaustive review of studies on anti-infection procedures revealed they were based more on laboratory data rather than in situ efficacy ( 14 ). The authors advised practitioners and researchers to consider system-level efficacy and not just the efficacy of a focal setting.…”
Section: Discussionmentioning
confidence: 99%
“…They report little to no benefit of either technology in reducing particle counts or inactivating microorganisms and in-fact demonstrated significant ozone generation with photocatalytic technology. This underscores the need for more practical investigation of accepted and novel technical solutions such as APC ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare Acquired Infections (HCAIs) continue to threaten the quality of patient care, and it is considered a major cause of morbidity and mortality worldwide [1]. In the United States, it is estimated that about 1.7 million people develop nosocomial-related illnesses yearly, and approximately 99,000 of them die [2]. Nosocomial pathogens are organisms causing diseases that are acquired from the hospital and healthcare environment within a few days of admission and are responsible for nosocomial infections [3], an endogenous bacterial flora is considered the main source of nosocomial infections, however, 20 to 40 % of nosocomial infections are caused by cross-contamination [4].…”
Section: Introductionmentioning
confidence: 99%
“…The high effectiveness of UV-C radiation in reducing a wide range of microorganisms, including MRSA, has been demonstrated, although predominantly in experimental studies [ 14 , 15 ]. As known for conventional chemical disinfectants, in vitro efficacy can vary greatly from real-world disinfection in a complex hospital setting depending on factors such as surface area, disinfectant concentration, contact time and type of microorganism [ 16 ]. Until now, mainly representative laboratory and test strains have been used for testing disinfection procedures.…”
Section: Introductionmentioning
confidence: 99%